Mensuração do grau de inovação no setor de carcinicultura do Rio Grande do Norte - Medeiros, Millayne Nogueira (Universidade Federal Rural do Semi-Árido, 2019)
Today innovation is fundamental in companies for competitive market survival and is a way to stay ahead of their competitors. Organizations need to maintain quality from the beginning of their processes to after-sales, satisfying their customers. The study of innovation is fundamental to understanding the level that organizations are in, comparing them with their competitors and identifying which dimensions need to be improved within their production processes. With this purpose, this research was carried out on the Degree of Innovation of the shrimp farming companies of Rio Grande do Norte. The state is a large shrimp producer and the number of breeding places has grown significantly in recent years. The research was carried out in 9 companies with a focus on shrimp farming in Rio Grande do Norte and on a scale of 1 to 5 it obtained the average of 3.2, identifying that these companies are occasional innovators, that is, they do not have an innovative routine and do not have an organization with innovative processes in the last 3 years.
Monografia
Keywords: Inovação; Rio Grande do Norte; Carcinicultura; Grau de inovação; Innovation; Rio Grande do Norte; Shrimp farming; Degree of Innovation; ENGENHARIAS::ENGENHARIA DE PRODUCAO